PENINGKATAN PENGETAHUAN ANAK SD KHAIRU UMMAH TENTANG PHBS DALAM MENYONGSONG ERA NEW NORMAL BANJARBARU 2021 - ISROWIYATUN D; ZAKIAH ZAKIAH; YUNIARTI YUNIARTI; RUSMILAWATY RUSMILAWATY; H.M. MUCHTAR (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2021)
To ensure that children remain safe, parents and schools must remind children to apply health protocols and make various preparations. Therefore, this activity was carried out by a team of midwifery lecturers and involved students, and the school, because Khairu Ummah Elementary School had already conducted face-to-face learning, it was important to facilitate children's knowledge and awareness in implementing health protocols, providing correct hand washing skills, motivating maintaining fitness by exercise together in an effort to promote and prevent transmission during the Covid-19 pandemic. The purpose of this activity is to increase children's knowledge and awareness in implementing health protocols (3M), to practice proper hand washing, and to improve children's fitness and health by doing gymnastics together. After the activity is carried out, it is hoped that it will provide benefits for children and the school. The target of community service activities for Khoiru Ummah Elementary School children is 37 people. The implementation method is counseling and practice, in collaboration and coordination with the Khoiru Ummah school. As a result, the leadership of the Khairu Ummah Foundation along with all teachers and students are very enthusiastic about welcoming this activity because it is very sustainable with prevention and refreshment efforts that can be used as habits and needs in carrying out the New Normal Era, especially in the implementation of offline learning activities (face-to-face meetings) by all Khairu Ummah student ABSTRAKUntuk memastikan anak tetap aman, orangtua dan pihak sekolah wajib mengingatkan anak untuk menerapkan protokol kesehatan dan melakukan berbagai persiapan. Oleh karena itu dilaksanakanlah kegiatan ini oleh tim dosen kebidanan dan melibatkan mahasiswa, dan pihak Sekolah, dikarenakan SD Khairu Ummah sudah melakukan pembelajaran tatap muka maka penting difasilitasinya pengetahuan dan kesadaran anak dalam menerapkan protokol kesehatan, memberikan keterampilan cuci tangan yang benar, memotivasi menjaga kebugaran dengan senam bersama dalam upaya promosi dan preventif penularan dimasa pandemi Covid-19. Tujuan kegiatan ini adalah untuk Meningkatan pengetahuan dan kesadaran anak dalam menerapkan protocol kesehatan (3M), Mempraktikkan cuci tangan yang benar, serta Meningkatkan kebugaran dan kesehatan anak dengan senam bersama. Setelah kegiatan dilaksanakan diharapkan dapat memberikan manfaat bagi anak dan pihak sekolah. Sasaran kegiatan pengabdian kepada anak Sekolah Dasar Khoiru Ummah berjumlah 37 orang. Metode pelaksanaan adalah penyuluhan dan praktik, bekerjasama dan koordinasi dengan pihak sekolah Khoiru Ummah. Hasilnya Pimpinan Yayasan Khairu Ummah beserta seluruh guru dan siswa sangat antusias menyambut kegiatan ini karena sangat berkesinambungan dengan upaya pencegahan dan penyegaran yang dapat dijadikan kebiasaan dan kebutuhan dalam menjalankan Era New Normal, terutama dalam pelaksanaan kegiatan pembelajaran yang bersifat Luring (Pertemuan tatap muka) oleh seluruh siswa Khairu Ummah